GATEKEEPING KEBIJAKAN REDAKSI PEMBERITAAN “TRAGEDI KANJURUHAN” PROGRAM SEA MORNING SHOW - Ovi Olivia Belida; Syubhan Akib (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The tragedy at Kanjuruhan Stadium in Malang has become a black record in domestic football matches. This tragedy claimed hundreds of lives, including women and children. This dark incident became the spotlight of various media, both media in Indonesia and foreign media. The editorial team of SEA Today News is concerned about the coverage of this tragedy, considering that football is a very popular sport in Indonesia. The purpose of this study was to find out the editorial policy gatekeeping that SEA Today News did in broadcasting the Kanjuruhan Tragedy. This researcher uses a case study method with a qualitative approach. The data collection technique used by the author is moderate participatory observation, where the writer has a balance between being an insider and an outsider, participating in some activities but not all. Besides that, structured interviews are used because the writer knows for sure what information will be obtained. In analyzing the editorial policy of SEA Today regarding the reporting of the Kanjuruhan Tragedy, the author uses the stages of the gatekeeping process by Shoemaker and Reese. The results of this study indicate that the gatekeeping process for the publication of the Kanjuruhan by the editorial staff of SEA Today begins with the selection of angles, script writing, selection of footage and sources determined by the program producers.